Lactiplantibacillus argentoratensis AGMB00912 protects weaning mice from ETEC infection and enhances gut health - Yoon, Ki-Nam; Yang, Jihye; Yeom, Seo-Joon; Kim, Sang-Su; Park, Jong-Heum; Song, Beom-Seok; Eun, Jong-Bang; Park, Seung-Hwan; Lee, Ju Huck; Kim, Hyeun Bum; Lee, Ju-Hoon; Kim, Jae-Kyung (Frontiers in Microbiology, 2024)
Maintaining a healthy intestinal environment, optimal epithelial barrier integrity, and balanced gut microbiota composition are essential for the growth performance of weaning pigs. We identified Lactiplantibacillus argentoratensis AGMB00912 (LA) in healthy porcine feces as having antimicrobial activity against pathogens and enhanced short-chain fatty acid (SCFA) production. Herein, we assess the protective role of LA using a weaning mouse model with enterotoxigenic Escherichia coli (ETEC) infection. LA treatment improves feed intake and weight gain and alleviates colon shortening. Furthermore, LA inhibits intestinal damage, increases the small intestine villus height compared with the ETEC group, and enhances SCFA production. Using the Kyoto Encyclopedia of Genes and Genomes and other bioinformatic tools, including InterProScan and COGNIZER, we validated the presence of SCFA-producing pathways of LA and Lactiplantibacillus after whole genome sequencing. LA mitigates ETEC-induced shifts in the gut microbiota, decreasing the proportion of Escherichia and Enterococcus and increasing SCFA-producing bacteria, including Kineothrix, Lachnoclostridium, Roseuburia, Lacrimispora, Jutongia, and Blautia. Metabolic functional prediction analysis revealed enhanced functions linked to carbohydrate, amino acid, and vitamin biosynthesis, along with decreased functions associated with infectious bacterial diseases compared to the ETEC group. LA mitigates the adverse effects of ETEC infection in weaning mice, enhances growth performance and intestinal integrity, rebalances gut microbiota, and promotes beneficial metabolic functions. These findings validate the functionality of LA in a small animal model, supporting its potential application in improving the health and growth performance of weaning pigs.